Gaya pembelajaran komputer guru pelatih kursus perguruan lepas ijazah Maktab Perguruan - Norazah Mohd. Nordin,; Shaari Osman, (penerbit ukm, 2005)
The purpose of this study was to determine the level of the preferred learning styles in the process of learning the applications of computer among post graduate teacher trainees in the Klang Valley as a case study. The main focus of the study was to determine the level of six preferred learning styles, which are audio, visual, tactile, kinestatic, group and individual in the process of learning the applications of computer. This study also focuses on the relationships between preferred learning styles with gender and options. This study was conducted upon 338 post graduate teacher trainees in colleges situated in the Klang Valley by using stratified sampling technique. A set of questionnaires was used to collect data and then analyzed by using descriptive and inferential statistics. In general, the study has shown that the level of the preferred learning styles in groups and kinestatic were high, and others were average. There was statistically significant relationship between the preferred learning styles in groups with gender. Other aspects of the preferred learning styles did not show any difference with respect to gender and options.